APPLICATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN CUSTOMER RELATIONSHIP MANAGEMENT TO IMPROVE CUSTOMER RETENTION - Loso Judijanto; Rachmadi Indra Praja; Syaiful Pakaya; Al-Amin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The application of artificial intelligence (AI) technology in customer relationship management (CRM) systems has become a key focus for companies seeking to improve customer retention in the digital age. Artificial intelligence oflers deep data analysis capabilities and personalisation of customer service, which are key in delivering a satisfying customer experience and increasing their loyalty. The research method used in this study is the literature research method. The results of this study show that the integration of AI in CRM has great potential in improving customer retention, but requires a careful implementation strategy to overcome the challenges and maximise the potential benefits.